STUDY OF SETTLEMENTARY AREA ARRANGEMENT AND FISHERY ACTIVITIES IN SEBANG BELAWAN FISHERMAN VILLAGE AS PART OF TOURISM - Yustina Rizki Hasibuan (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to examine the arrangement of residential areas and fisheries activities in Seberang Belawan Fishermen's Village, as part of sustainable tourism development. This area has great potential in the fisheries and tourism sectors, but has not been properly regulated, so integrated arrangement is needed. The method used in this study is a descriptive approach with qualitative analysis, which involves field studies, interviews with the community, and secondary data collection related to policies and existing conditions of the area. The results of the study indicate that the current condition of the area faces various challenges, including limited infrastructure, suboptimal natural resource management, and a lack of integration between fisheries and tourism activities. Area planning based on the principles of sustainability is needed to integrate these two sectors. The recommended area planning model includes clear zoning between fisheries, residential, and tourism areas, development of environmentally friendly infrastructure, community empowerment through training and education, and participatory natural resource management. With appropriate planning, it is hoped that Seberang Belawan Fishermen's Village can optimize its fisheries and tourism potential in a sustainable manner, which in turn can improve the welfare of local communities and maintain environmental sustainability. This research provides recommendations for more structured and sustainable regional development, by involving all parties in the management and decision-making process.